ANALOGY OF THE USES OF MEDICINAL SPECIES IN CUBA AND THE STATE OF BAHIA, BRAZIL IN THE LAST DECADE - Gato Hernandez, Misleidy; Sousa Dreger Nery, Felipe; Maria Chaves, Joselisa; Cantillo Perez, Taimy (Floresta, 2024)
Since the dawn of humanity, plants have been used to alleviate and cure diseases. Since biological diversity is precisely different in each location as it depends mainly on the climate and relief and therefore it is assumed that the development of phytotherapy or alternative medicine based on plants developed unevenly from the plants that had their disposal as well as the treatment priorities needed. Taking into account that Cuba and the state of Bahia have a similar climate, as well as a similar number of inhabitants, they were taken as the objective in this study, with a greater discrepancy in terms of territorial extension. The main purpose of this study is to understand the relationships of ethnobotany in medicinal plants in the state of Bahia, Brazil and Cuba. The method of bibliographical review of publications available from the last decade and which were accessible in the Scopus, Google Scholar, SciELO, PubMed databases was used, taking into account that these must be free and refer to the subject of study in question to be selected. The result shows that the publications place Cuba well above the number of studies published on the subject when the comparison is made. There are also coincidences in both territories in relation to the diseases most treated with medicinal plants, the most used parts of the plants and the families that cover most of the species described in the reviewed research. Obtaining a total of species (247), 111 in Cuba and 136 mentioned in the studies reviewed in the Brazilian state. Leaves are the most used parts and the Lamiaceae family is the most popular. .